Postural control in girls with adolescent idiopathic scoliosis while wearing a Chêneau brace or performing active self-correction: a pilot study - Piątek, Elżbieta; Kuczyński, Michał; Ostrowska, Bożena (PeerJ, 2019)
Background It is known that adolescent idiopathic scoliosis (AIS) is often accompanied by balance deficits. This reciprocal relationship must be taken into account when prescribing new therapeutic modalities because these may differently affect postural control, interacting with therapy and influencing its results. Objective The purpose was to compare postural control in girls with AIS while wearing the Chêneau brace (BRA) or performing active self-correction (ASC) with their postural control in a quiet comfortable stance. Methods Nine subjects were evaluated on a force plate in three series of two 20-s quiet standing trials with eyes open or closed; three blocks were randomly arranged: normal quiet stance (QST), quiet stance with BRA, and quiet stance with ASC. On the basis of centre-of-pressure (COP) recordings, the spatial and temporal COP parameters were computed. Results and Discussion Performing ASC was associated with a significant backward excursion of the COP mean position with eyes open and closed (ES = 0.56 and 0.65, respectively; p < 0.05). This excursion was accompanied by an increase in the COP fractal dimension (ES = 1.05 and 0.98; p < 0.05) and frequency (ES = 0.78; p = 0.10 and ES = 1.14; p < 0.05) in the mediolateral (ML) plane. Finally, both therapeutic modalities decreased COP sample entropy with eyes closed in the anteroposterior (AP) plane. Wearing BRA resulted in ES = 1.45 (p < 0.05) while performing ASC in ES = 0.76 (p = 0.13). Conclusion The observed changes in the fractal dimension (complexity) and frequency caused by ASC account for better adaptability of patients to environmental demands and for their adequate resources of available postural strategies in the ML plane. These changes in sway structure were accompanied by a significant (around 25 mm) backward excursion of the mean COP position. However, this improvement was achieved at the cost of lower automaticity, i.e. higher attentional involvement in postural control in the AP plane. Wearing BRA may have an undesirable effect on some aspects of body balance.
Keywords: Adolescent idiopathic scoliosis; Chêneau brace; Active self-correction; Postural control